The Effect of Flipped E- learning strategy in Self– efficacy of Learning for The University Student - AL- Zubi, Emad; Alsaydah, Reham; Attiat, Madher (Dirasat: Human and Social Sciences, 2021)
This study aims at investigating the effect of teaching using flipped e-learning strategy on improving self-efficiency of learning among university students. The sample of the study consisted of (102) students who were studying at BAU in Salt, Jordan. The sample was then divided into two groups; experimental and control. To achieve the aim of the study, a software was designed based on the flipped e-learning strategy and a scale of self-efficiency was developed. The results showed that there was a statistically significant effect on using the flipped e-learning strategy on the following dimensions: Self-organization, self-control, and self-evaluation. The results also showed that there were statistically significant differences in self-efficiency of learning on the self-control and self-evaluation dimensions in favor of the experimental groups due to the academic level (i.e. second-year students and above). Further, there were not any statistically significant differences in the self-efficiency of learning on self-organization dimension among the experimental group due to the academic level. Likewise, there were no statistically significant differences were revealed in the self-efficiency of learning on the sub-dimensions; self-organization, self-control and self-evaluation among the experimental group due to the cumulative average.